Pandemic preparedness and response: beyond the Access to COVID-19 Tools Accelerator. Issue 1 (17th January 2023) - Saxena, Abha; Baker, Brook K; Banda, Amanda; Herlitz, Anders; Miller, Jennifer; Karrar, Karrar; Fleurbaey, Marc; Chiwa, Esther; Atuire, Caesar Alimisnya; Hirose, Iwao; Hassoun, Nicole
Abstract : Nationalism has trumped solidarity, resulting in unnecessary loss of life and inequitable access to vaccines and therapeutics. Existing intellectual property (IP) regimens, trade secrets and data rights, under which pharmaceutical firms operate, have also posed obstacles to increasing manufacturing capacity, and ensuring adequate supply, affordable pricing, and equitable access to COVID-19 vaccines and other health products in low-income and middle- income countries. We propose: (1) Implementing alternative incentive and funding mechanisms to develop new scientific innovations to address infectious diseases with pandemic potential; (2) Voluntary and involuntary initiatives to overcome IP barriers including pooling IP, sharing data and vesting licences for resulting products in a globally agreed entity; (3) Transparent and accountable collective procurement to enable equitable distribution; (4) Investments in regionally distributed research and development (R&D) capacity and manufacturing, basic health systems to expand equitable access to essential health technologies, and non-discriminatory national distribution; (5) Commitment to strengthen national (and regional) initiatives in the areas of health system development, health research, drug and vaccine manufacturing and regulatory oversight and (6) Good governance of the pandemic prevention, preparedness and response accord. It is important to articulate principles for deals that include reasonable access conditions and transparency in negotiations. We argue for an equitable, transparent, accountable new global agreement to provide rewards for R&D but only on the condition that pharmaceutical companies share the IP rights necessary to produce and distribute them globally. Moreover, if countries commit to collective procurement and fair pricing of resulting products, we argue that we can greatly improve our ability to prepare for and respond to pandemic threats.